The Principle of Permanent Sovereignty over Natural Resources and Its Modern Implications - Hofbauer, Jane A., 1984- (2010)
This thesis aims at, firstly, giving an overview over the historical development of the principle of permanent sovereignty over natural resources to enable an understanding for the reasons paving the way for a change of its scope. Secondly, an outline over the most important elements of PSNR will be provided for in Chapter II. By means of case-studies, recent invocations of the principle with regard to foreign investments in South America will provide a first example of how the principle can be envisioned to be utilized in the 21st century. Furthermore, the relationship of the principle, as a tool aimed at ensuring sovereignty, with evolved environmental norms, which often aim at limiting sovereignty, will be determined. Finally, the applicability of the principle of PSNR to indigenous peoples shall be analyzed. Concerning the findings thereof, case-studies of Greenland and indigenous and tribal peoples in Suriname will be examined to compare the theoretical arguments to practical examples of implementation.